'The Dagger of Dispossession Will Be Ripped Out': The Malvinas/Falkland Islands in Argentine Song (1941–82). Issue 4 (17th November 2021) - Carassai, Sebastián
Abstract: In April 1982, Great Britain and Argentina went to war over the Falkland Islands/Malvinas. On 14 June, the defeated Argentine military began the evacuation of the Islands. Most Argentines came to view this short war as an absurd adventure entered into by a military dictatorship in decline trying to cling on to power. Yet by analysing Argentine songs about the Malvinas from 1941 to 1982, this article shows that the national imaginary had long included ideas of sovereignty usurped and captive islands awaiting redemption. Argentine songs about the Malvinas, I maintain, can be analysed as expressions of an 'emotional community' around the Islands. By examining the emphases, constants and changes in the songs emerging from that community, we get a clearer picture of how ideas about the territory and its recovery changed over time.